UNGRAMMATICAL SENTENCES: A GRAMMATICAL ERROR ANALYSIS ON ARCHITECTS STUDENTS’ CORPUSES OF PONTIANAK STATE POLYTECHNIC - Hilda Mutia Sari; Rafika Nurhidayah (Jurnal Ilmiah Spectral, 2022)
Writing has become a challenging skill for EFL or ESL students to overcome. It is not only required the ability to compose a good writing but also a deep layer known as the grammatical aspect. Understanding grammar is very important for building good sentences. Hence, this study aims to find out the most grammatical error found in students’ corpuses and classify the students’ error. To generate this purpose, the researcher explored the grammatical mistakes made with the aid of using college students at the first semester of Pontianak State Polytechnic as the sample of research. This study was conducted using descriptive research using students’ corpus as the data collection. The results of this study discovered that the addition error is the most frequent type of error made based on the frequency on the percentage that was 39,02%. Furthermore, this kind of error is classified as substantial. As for the other types of errors made by students, namely mis formation with the total of errors as 35.36%, omission of error as 23.17% and error in disordering as 2.44%. It can be concluded that the students made errors due to their background of knowledge and their lack of understanding of English structure.